Characterization of Resistance Mechanisms in Faba Bean (Vicia faba) against Broomrape Species (Orobanche and Phelipanche spp.) - Rubiales, Diego; Rojas-Molina, Maria M.; Sillero, Josefina C. (Frontiers in Plant Science, 2016)
Faba bean (Vicia faba) production in Mediterranean and Near East agriculture is severely constrained by broomrape infection. The most widely distributed broomrape species affecting faba bean is Orobanche crenata, although O. foetida and Phelipanche aegyptiaca are of local importance. Only moderately resistant cultivars are available to farmers. Rizotrons studies allowed the dissection of resistance components in faba bean accessions against the very infective species O. crenata, O. foetida var. broteri and P. aegyptiaca, and to the inappropriate P. ramosa and O. foetida var. foetida. Results confirm that some levels of incomplete resistance are available, resulting in a reduced number of broomrape tubercles successfully formed per faba bean plant. Interestingly, the intermediate levels of resistance of cv. Baraca were operative against all broomrape populations and species studied, confirming previous reports on the stability of resistance of Baraca in field trials in different countries. Low induction of seed germination played a major role in the resistance against the inappropriate O. foetida var. foetida but not against the also inappropriate P. ramosa, neither to the infective species O. crenata, O. foetida var. broteri, or P. aegyptiaca. Negative tropism of germinated seeds with radicles growing away from faba bean roots was marked for both inappropriate species but was not observed in any of the infective species. Also, a proportion of radicles that had successfully contacted faba bean roots became necrotic, failing in starting tubercle development, particularly frequent for the two inappropriate species. Such necrosis was significant also on radicles contacting resistant faba bean accessions, being particularly relevant for Spanish O. crenata population, and lower although still significant in some accessions against Syrian O. crenata and P. aegyptiaca, suggesting that this might also be an operative mechanism to be selected and further exploited in faba bean resistance breeding. Even formed broomrape tubercles might later become necrotic, particularly in the case of some of the resistant faba bean accessions to the Spanish O. crenata and to P. aegyptiaca but not to the very infective Syrian O. crenata or O. foetida var. broteri.